МЕТОДИКА ВИЗНАЧЕННЯ ФУНКЦІОНАЛЬНОГО КЛАСУ ХВОРОГО НА СИСТЕМНИЙ ЧЕРВОНИЙ ВОВЧАК - У. О. Абрагамович; О. О. Абрагамович; Л. В. Циганик; М. Л. Фармага; О. В. Синенький (World Science, 2020)
The correct and comprehensive assessment of the condition of patients with systemic lupus erythematosus and typical SLE-related multi-organ and multisystemic lesions requires developing a new integrated measure of their condition. Such measure should take into account modern advances in understanding the causes and pathogenesis of the disease, while assessing the degree of its activity, its progression, the number and severity of syntropic comorbid lesions of organs and systems, and formulating a clinical diagnosis.Objective. To develop the method of assigning functional classes to patients with systemic lupus erythematosus.Materials and methods. The research was conducted in three successive steps: the purpose of the first step was toconduct a review of literature, i.e. to analyze retrospectively 130 sources of literature in English and Ukrainian using content analysis, systemic and comparative analysis, bibliographic analysis of relevant publications on SLE grading, especially by its severity, in PubMed, Medline, Cochrane Library, and Research Gate databases. The purpose of the second step was to develop a method of assigning functional classes to patients with SLE based on modern literature and our own clinical experience. The purpose of the third step was to demonstrate examples of its application.Results and discussion. There is an obvious need to assess SLE activity, its progression, the number and severity of syntropic comorbid lesions of organs and systems, formulate a clinical diagnosis and assign functional classes to patients with SLE based on easily calculated integrated measures for each patient. However, the review of the literature showed that such a measure had not been developed yet. The proposed method includes three phases. The purpose of the first phase is to assess the activity of systemic lupus erythematosus according to the SELENA-SLEDAI total outcome and assign the appropriate number of points: inactive systemic lupus erythematosus - 0 points, the mild activity of SLE – 1 point, the moderate activity of SLE – 2 points, the high activity and very high activity of SLE - 3 points. The purpose of the second phase is to assess the progression of systemic lupus erythematosus and assign the appropriate number of points: patients with chronic SLE – 1 point, patients with subacute SLE – 2 points, patients with acute SLE – 3 points. The purpose of the third phase was to assess the syntropic comorbid lesions of organs and systems and assign the appropriate number of points: no lesions – 0 points, a slight deviation from normality that does not require treatment – 1 point; lesions that require medical correction – 2 points; severe organ failure that requires immediate treatment – 3 points. The number of points (total score) that can be assigned to a patient with systemic lupus erythematosus ranges from 0 to 45. If the total score is 0, then the patient should be classified as being in remission. If the total score ranges from 1 to 15 points, then the patient should be classified as being in functional class I (the condition of the patient with SLE should be graded as mild). If the total score ranges from 16 to 26 points, then the patient should be classified as being in functional class II (the condition of the patient with SLE should be graded as moderate).If the total score ranges from 27 to 45 points, then the patient should be classified as being in functional class III (the condition of the patient with SLE should be graded as severe). This method takes into account the disease activity, its progression, the number and severity of syntropic comorbid lesions of organs and systems. The total score interpreted according to the defined ranges allows us to assess the condition of patients with SLE in general, i.e. to assign functional classes to them, objectivize expert assessments, determine the dynamics of disease progression and the effectiveness of treatment.Conclusions. We have developed the method to assess the condition of patients with systemic lupus erythematosus in a simple and objective manner by calculating integrated measure that denotes the functional class of patient with SLE. This method takes into account the results of other research studies published in scientific Ukrainian and foreign journals, as well as the results of our research studies. It takes into account the disease activity, its progression, the number and severity of syntropic comorbid lesions of organs and systems. The method can be successfully applied in clinical practice to optimize expert assessments of patient condition, to analyze the dynamics of disease progression and the effectiveness of treatment.